Mission impossible: Vertical collaboration in Ukraine - Taras Gagalyuk; Jon Hanf (Banwa, 2008)
Food products are increasingly being produced in vertically coordinated networks. While one could argue that supply chain networks and their management are of greater interest in the developed countries, in-depth interviews with agribusiness experts provide evidence that the interest in supply chain management is even greater in the transitional economies. A study of food businesses in Ukraine reveals a number of challenges and barriers supply chain networks face in the transitional economies, the most significant of which are cooperation and coordination issues.
Keywords: 330; agribusiness; chain management; cooperation; coordination; supply chain networks; Ukraine